Optimization Criteria in Mössbauer Spectroscopy - Bravo J.A. (2003)
The authors acknowledge the support of the Consejo Superior de Investigaciónand the Facultad de Ciencias Físicas of the Universidad Nacional Mayor de SanMarcos, and of our Consejo Nacional de Ciencia y Tecnología, CONCYTEC, Perú. We are grateful to the personnel of our Mössbauer and Soils Laboratories for helpwith the equipment.